Age and growth of the amazonian migratory catfish Brachyplatystoma rousseauxii in the Madeira River basin before the construction of dams - Hauser, Marília; Dória, Carolina Rodrigues da Costa; Melo, Larissa R.C.; Santos, Ariel R.; Ayala, Daiana Mendes; Nogueira, Lorena D.; Amadio, Sidineia Aparecida; Fabré, Nídia Noemí; Torrente-Vilara, Gislene; García-Vásquez, Áurea; Renno, Jean François; Carvajal-Vallejos, Fernando Marcelo; et al. (Neotropical Ichthyology, 2018)
The goliath catfish Brachyplatystoma rousseauxii has crucial economical and ecological functions in the Amazon basin. Although its life history characteristics have been studied in the Amazon, there is little information in the Madeira River basin, which holds genetically distinct populations and where dams were recently built. Using fish collected in Bolivia, Brazil and Peru, this study provides a validation of growth rings deposition and details the growth patterns of B. rousseauxii in the Madeira before the dams’ construction. Age structure and growth parameters were determined from 497 otolith readings. The species exhibits two growth rings per year and sampled fish were between 0 and 16 years old. In the Brazilian portion of the basin, mainly young individuals below 5 years old were found, whereas older fish (> 5 years) were caught only in the Bolivian and Peruvian stretches, indicating that after migrating upstream to reproduce, adults remain in the headwaters of the Madeira River. Comparing with previous publications, B. rousseauxii had a slower growth and 20 cm lower maximum standard length in the Madeira River than in the Amazon River. This study provides a baseline for future evaluation of changes in population dynamics of the species following dams closure. © 2018 Sociedade Brasileira de Ictiologia.